Debt by Design: Exploring Market Forces Behind Leverage in Two Economies - Houshang Habibniya; Suzan Dsouza; Naliniprava Tripathy (Ital Publication, 2026)
Abstract This study investigates the determinants of capital structure by comparing firms listed on two prominent global stock indices: the S&P 500 (United States) and the NSE CNX 500 (India). Specifically, it examines how firm-specific factors—such as liquidity, asset tangibility, and sustainability practices—influence leverage decisions within differing economic and institutional contexts. Drawing on a comprehensive dataset of 3,575 firm-year observations from 406 S&P 500 companies and 4,180 observations from 419 NSE CNX 500 firms between 2011 and 2021, the analysis employs Two-Stage Least Squares (2SLS) regression, the Generalized Method of Moments (GMM), and a series of diagnostic tests addressing heteroskedasticity and model robustness. The empirical results indicate that liquidity, tangibility, and sustainability performance significantly affect firms’ capital structure decisions. Moreover, growth opportunities and profitability also play key roles. Cross-country differences highlight the influence of macroeconomic conditions and financial system structures on leverage behavior. This research enriches the capital structure literature by offering a comparative, cross-national perspective and provides actionable insights for corporate managers, investors, and policymakers seeking to optimize capital structure in diverse financial environments